A Qualitative analysis of teacher feedback and student motivation in statistics didactic design - Tina Yunarti; Annisa Mutiarani; Santy Setiawati; Niki Pujarwati (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
Teacher feedback plays an important role in supporting students’ learning motivation, particularly when it is integrated into the learning process through a well-structured didactic design. However, feedback in statistics learning is often still predominantly evaluative and has not been systematically used to guide students’ learning processes. This study aims to identify the types of teacher feedback provided to students in Class VII-A of SMP Negeri 26 Bandar Lampung and to describe students’ learning motivation after receiving feedback within a statistics didactic design. This research employed a qualitative case study design involving 31 seventh-grade students in the even semester of the 2023/2024 academic year. Data were collected through field notes, Likert-scale questionnaires on teacher feedback and student learning motivation, and interviews. The data were analyzed descriptively to identify patterns of teacher feedback and students’ motivational responses. The findings indicate that verbal feedback was the dominant form of feedback provided by the teacher. The most frequently observed feedback indicators were timely, specific, and process-focused feedback. In addition, students with high and moderate mathematical ability tended to show higher learning motivation than students with low mathematical ability. These findings suggest that process-oriented teacher feedback can support students’ motivation in learning statistics, especially when it is embedded in a structured didactic design.